A method of determining the carbon emission reduction contribution of regional distribution networks based on spherical fuzzy sets - Du, Puliang; Yang, Miaoheng; Hu, Wei; Wang, Pengfei; Xing, Qiang (Frontiers in Energy Research, 2024)
To delve into the pivotal role of regional distribution networks (RDNs) in fostering low-carbon development, an innovative perception methodology is proposed, which firstly constructs an evaluation framework encompassing various dimensions, secondly integrate Spherical Fuzzy Sets (SFSs) with the Best-worst Method (BWM), enabling the precise calculation of indicator weight parameters. Subsequently, we employ the Measurement of Alternatives and Ranking according to Compromise Solution (MARCOS) with SFS to process and synthesize decision-making information. Finally, in order to prove the practicability of the proposed method, the contribution of the regional distribution network to carbon emission reduction is evaluated in Shanghai.